Modification of the interface between TiO2 and electrolyte toward higher efficiency dye sensitized solar cells - Wang, Xiu (2014)
The objective of this thesis is to improve the photovoltaic performance of Dye-Sensitized Solar Cells (DSSCs) by modifying the interface between TiO2 photoanode and electrolyte (iodide/triiodide as redox). This thesis is featured with two main approaches for improving the performance of DSSCs: a direct modification on TiO2 surface through surface treatment and molecular passivation and an indirect modification to alter the TiO2 surface charge through adding nanoparticles such as hydrotalcite and silica into the electrolyte. Results obtained indicate that the investigated approaches are promising in improving the photovoltaic performance of DSSCs in different aspects. This study started with direct modification of TiO2 photoanode through surface treatment using a novel, simple, safe and effective TiF4 hydrolysis treatment instead of the conventional TiCl4 treatment. The efficiency was enhanced by 22% compared with the reference device. To further improve the efficiency and address the dark current problem, another direct modification through the passivation of self assembled monolayer (C18H37SiX3, X is H, OCH3 or Cl) on sensitized TiO2 was applied and investigated. Besides the target on interfacial modification, to address the issues of difficult handling and leakage caused by liquid electrolyte, nanoparticles were introduced as additives to transform the liquid into a quasi-solid electrolyte and meanwhile indirectly altering the TiO2 surface charge. Silica nanoparticles were introduced to gel the ionic electrolyte. A detailed study was carried out on how tuning silica nanoparticles affect the device performance and charge transfer at the counter electrode-electrolyte interface in binary ionic liquids based electrolyte. With synthetic nitrate-hydrotalcite as gelator, 10% improvement of efficiency was achieved. Following this, the effect of anions inside the hydrotalcite was also investigated. The results indicated that proper selection of hydrotalcite compounds produced quasi-solid gel electrolyte, simultaneously improving the power conversion efficiency of the solar cells.